2018
DOI: 10.3892/ijmm.2018.3897
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-194-5p inhibits cell proliferation, migration and invasion in breast cancer by regulating the Wnt/β-catenin signaling pathway

Abstract: Breast cancer is a major public health concern, due to its increasing incidence and limited effective treatment. The present study aimed to investigate the expression of microRNA (miR)-194-5p and its roles in breast cancer. The expression levels of miR-194-5p and SRY-box 17 (SOX17) mRNA were detected in breast cancer tissues and cell lines by reverse transcription-quantitative polymerase chain reaction. The protein expression levels were determined by western blotting. In addition, MTT, colony formation, scrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…In BC, miR‐194‐5p was described as having tumor‐suppressive roles by inhibiting proliferation and migration in vitro and in vivo (Le et al , ). However, a recent paper demonstrated that miR‐194‐5p enhances cell proliferation, migration, and invasion in different BC cell lines via Wnt/β‐catenin pathway regulation (Yang et al , ). These contradicting reports may be a consequence of the multitude of genes and functions that one single miRNA can regulate and of the multiple factors and cellular contexts that influence their expression (Dykxhoorn, ).…”
Section: Discussionmentioning
confidence: 99%
“…In BC, miR‐194‐5p was described as having tumor‐suppressive roles by inhibiting proliferation and migration in vitro and in vivo (Le et al , ). However, a recent paper demonstrated that miR‐194‐5p enhances cell proliferation, migration, and invasion in different BC cell lines via Wnt/β‐catenin pathway regulation (Yang et al , ). These contradicting reports may be a consequence of the multitude of genes and functions that one single miRNA can regulate and of the multiple factors and cellular contexts that influence their expression (Dykxhoorn, ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-194 reduces nuclear accumulation of β-catenin and inhibits the Wnt signaling pathway in gastric cancer (35). In addition, the proliferation and infiltration of breast cancer cells are inhibited by knockout of miR-194, which regulates the Wnt/β-catenin signaling pathway (36). Miao et al (37) also revealed that miR-194 targets cadherin 2 (CDH2) to inhibit cell expansion and promote apoptosis in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Interestingly, Yang et al found that miR-194-5p was up-regulated in breast cancer tissues and silence of miR-194-5p inhibited cell proliferation and metastasis via targeting SOX17. 28 Meanwhile, decreased miR-194-5p was implicated in sunitinib resistance in human renal cell carcinoma and paclitaxel resistance in ovarian cancer. 29,30 These studies revealed a complex function and molecular basis of miR-194-5p, yet its role in OSCC still remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%